Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1115/1.4029747
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Aortic Root Geometry on Flow Characteristics of a Prosthetic Heart Valve

Abstract: In this paper, performance of aortic heart valve prosthesis in different geometries of the aortic root is investigated experimentally. The objective of this investigation is to establish a set of parameters, which are associated with abnormal flow patterns due to the flow through a prosthetic heart valve implanted in the patients that had certain types of valve diseases prior to the valve replacement. Specific valve diseases were classified into two clinical categories and were correlated with the correspondin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 39 publications
(39 reference statements)
0
17
0
Order By: Relevance
“…However, these values are based on a simple laminar profile approximation resulting in the effect of turbulence being ignored. Using particle image velocimetry (PIV) on different aortic root geometries (normal, dilated, constricted), Barannyk and Oshkai investigated the turbulence stresses and found the peak turbulence stress to be ~1200 dyne/cm 2 . Gunning et al found the similar level of turbulent stress (up to 2300 dyne/cm 2 ) from their heart valve study.…”
Section: Discussionmentioning
confidence: 99%
“…However, these values are based on a simple laminar profile approximation resulting in the effect of turbulence being ignored. Using particle image velocimetry (PIV) on different aortic root geometries (normal, dilated, constricted), Barannyk and Oshkai investigated the turbulence stresses and found the peak turbulence stress to be ~1200 dyne/cm 2 . Gunning et al found the similar level of turbulent stress (up to 2300 dyne/cm 2 ) from their heart valve study.…”
Section: Discussionmentioning
confidence: 99%
“…The peak inflow velocity was ~1.2 m/s and the density of blood was set to ρ = 1080 kg/ m 3 . The blood also was considered to be both Newtonian with the viscosity of 0.0035 kg/(m.s) and non-Newtonian based on generalized Carreau-Yasuda model [14]. This lead to an inlet peak Reynolds number…”
Section: Models and Methodsmentioning
confidence: 99%
“…The current computational study provides new quantitative information on blood flow characteristics, plus forces and moments acting on the leaflets of bileaflet mechanical heart valves at different levels of leaflet dysfunctionality during peak systolic flow. Model improvements compared to previous studies include: A more realistic aortic sinuses geometry (compared to References [ 41 , 42 ]), addition of the valve ring to the model (compared to References [ 43 , 44 ]), and creation of a 3-D model instead of a 2-D model (compared to References [ 2 , 13 , 45 ]). The study quantified important hemodynamic characteristics (such as principle stresses) that are not measurable using currently available standard diagnostic tools.…”
Section: Introductionmentioning
confidence: 99%